Cytotoxic B Cells in Relapsing-Remitting Multiple Sclerosis Patients - Boldrini, Vinícius O.; Marques, Ana M.; Quintiliano, Raphael P. S.; Moraes, Adriel S.; Stella, Carla R. A. V.; Longhini, Ana Leda F.; Santos, Irene; Andrade, Marília; Ferrari, Breno; Damasceno, Alfredo; Carneiro, Rafael P. D.; Brandão, Carlos Otávio; et al. (Frontiers in Immunology, 2022)
Background: Emerging evidence of antibody independent functions, as well as the clinical efficacy of anti-CD20 depleting therapies, have helped to reassess the contribution of B cells during Multiple Sclerosis (MS) pathogenesis. Objective: To investigate whether CD19+ B cells may share expression of the serine-protease granzyme-B (GzmB), resembling classical cytotoxic CD8+ T lymphocytes, in the peripheral blood from relapsing-remitting MS (RRMS) patients. Methods: 104 RRMS patients during different treatments and 58 healthy donors were included. CD8, CD19, Runx3, and GzmB expression were assessed by flow cytometry analyses. Results: RRMS patients during Fingolimod (FTY) and Natalizumab (NTZ) treatment showed an increased percentage of circulating CD8+GzmB+ T lymphocytes when compared to healthy volunteers. An increase in circulating CD19+GzmB+ B cells was observed in RRMS patients during FTY and NTZ therapies when compared to Glatiramer (GA), untreated RRMS patients, and healthy donors, but not when compared to Interferon-β (IFN). Moreover, regarding Runx3, the transcriptional factor classically associated with cytotoxicity in CD8+ T lymphocytes, the expression of GzmB was significantly higher in CD19+Runx3+-expressing B cells when compared to CD19+Runx3- counterparts in RRMS patients. Conclusions: CD19+ B cells may exhibit cytotoxic behavior resembling CD8+ T lymphocytes in MS patients during different treatments. In the future, monitoring "cytotoxic" subsets might become an accessible marker for investigating MS pathophysiology and even for the development of new therapeutic interventions.